Age and provenance of the Chaung Magyi Group, Yeywa Dome, Myanmar, based on U-Pb dating of detrital zircons - Romana Dew (2019)
© 2019 The unfossiliferous Chaung Magyi Group of the Northern Shan Plateau of Myanmar, comprises metasedimentary rocks, in particular greywacke, slates, phyllites and schists, of inferred Proterozoic age that unconformably underlie the late Cambrian Pangyun Formation. To address the problem of the youngest stratigraphic extent of the group, four samples of the Chaung Magyi Group from the Yeywa Dome, East of Kyaukse, Mandalay Division, were collected for U-Pb dating of detrital zircons. Based on the youngest detrital zircons present in sandstone samples from the western Yeywa Dome area, at least the upper part of the Chaung Magyi Group is of latest Proterozoic age and possibly extends to the late Cambrian (~500 Ma). Comparison of detrital zircon age-frequency histogram distributions show only slight differences in distributions of detrital zircons in the Cambrian of NW Thailand and the Chaung Magyi Group samples (Sibumasu Terrane), with a concentration of ages between 1300 Ma and 820 Ma, with two major peaks at 1086 Ma and 1022 Ma. A younger Cryogenian age peak at 647 Ma is also observed. A spread of older concordant ages ranges from 3093 Ma to 1406 Ma. The minimum depositional age for the Chaung Magyi Group of the west of the Bawdwin Mine (982 Ma) based on ages of cross-cutting dykes (reported in Mitchell, 2018), and the maximum depositional age for Yeywa Dome (~600–500 Ma) based on detrital zircons suggest the age difference (~>400 my) is too great for the Chaung Magyi Group to be considered a single group, the dyke ages require re-investigation.